Strategi Pembinaan Aqidah dan Akhlak pada Anak Disabilitas (Tunagrahita) di SLB Kota Banda Aceh - Umam, Khairul (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2023)
Intellectually disabled children are children who have an intelligence level that is below average and has difficulty in adapting their behavior as they grow. SLB TNCC Banda Aceh is a special education program that aims to support the development and expression of the potential of students with special needs, including developing aqidah and morals. Therefore, the role of school principals and teachers is crucial in developing the faith and morals of children, especially tunagrahita children. The aims of the research are: 1) to find out strategies for fostering aqidah and morals in children with disabilities (Tunagrahita) at SLB TNCC Banda Aceh; 2) to find out the supporting and inhibiting factors for strategies for fostering faith and morals in children with disabilities (Tunagrahita) at SLB TNCC Banda Aceh. The research method used in this study is a descriptive-qualitative approach. The research subjects consisted of 7 people, namely: the principal, 2 class teachers and 4 mentally retarded children. Data collection techniques were carried out using observation, interviews, and documentation. The research results found that 1) there are four strategies used by teachers in developing the aqidah and morals of tunagrahita children at SLB TNCC Banda Aceh City, those are through habituation, exemplary strategies, discipline strategies, and through mauidzah (giving advice) strategies. 2) There are several obstacles in the strategy of developing aqidah and morals for mentally retarded children at SLB TNCC Banda Aceh. Tunagrahita children are difficult to talk to because they are not very capable of speaking. Hence, the children prefer to remain silent, and it is also related to the background of the children, who come from a variety of different backgrounds and families, so they often bring behavioral patterns or traditions from the environment before they join the school. The solutions provided are: 1) Holding a meeting with the child's parents; this aims to guide parents on the best way to support their children who have special needs for mental retardation. 2) Implement training and habituation strategies, because with the habituation strategies that are implemented, children continue to repeat or practice the habits they do. Keywords: Development Strategy, Aqidah and Morals, Tunagrahita Children